Common Familial Effects on Ischemic Stroke and Myocardial Infarction: A Prospective Population-Based Cohort Study - Kasiman, Katherine; Lundholm, Cecilia; Sandin, Sven; Malki, Ninoa; Sparén, Pär; Ingelsson, Erik (Frontiers in Cardiovascular Medicine, 2014)
Background: Recent genome-wide association studies suggest some overlap of genetic determinants of ischemic stroke (IS) and myocardial infarction (MI). This study aimed to assess shared familial risk between IS and MI in a large population-wide cohort study. Methods: Study participants free of IS and MI and their affected siblings were extracted from the Swedish Hospital Discharge and Cause of Death Registers between 1987 and 2007, forming an exposed sib-pair. They were matched by birth year of both siblings and calendar period to up to five unexposed sib-pairs. Stratified Cox regression analyses were used to assess familial risk of MI and IS in those exposed to having a sibling with IS (n=31,659) and MI (n=62,766) respectively, compared to unexposed (n=143,728 and 265,974). Results: The overall risk of MI when exposed to having a sibling with IS was statistically significantly increased (RR, 1.44; 95% CI, 1.34-1.55, p<0.001) to a similar extent as risk of IS when exposed to having a sibling with MI (RR, 1.41; 95% CI, 1.32-1.50, p<0.001). The familial risks were similar in full siblings for both groups (RR for MI, 1.46; 95% CI, 1.35-1.58, p<0.001; and RR for IS, 1.40; 95% CI, 1.30-1.40, p<0.001) and half siblings (RR for MI, 1.29; 95% CI, 1.05-1.59, p<0.001; and RR for IS, 1.38; 95% CI, 1.16-1.65, p<0.001). Conclusion: This large, population-wide study indicates that there is considerable overlap of familial risk between ischemic stroke and myocardial infarction.